Siberian Animal Style as a Conceptual Basis for the Conversion of Traditional Artistic Heritage into Cultural Industries - Margarita I. Gomboeva (Гуманитарный вектор)
The process of acquiring the author’s style, its semantic distinctive features, and the creation of the author’s identity is a fundamental problem for artists. The paper is devoted to the analysis of the artist’s native culture code influence on the creative concept and artistic language. Artistic inversion is important ‒ the inverse representation of the cultural code in the artist’s work. We consider artistic, pictorial inversion as a form of the artistic conceptualization. It contributes to the successful understanding of the connotations and intentions of the artist’s work by his audience. An analysis of Namdakov’s work allowed us to conceptualize the representation problem of the cultural code in Far East peoples’ contemporary art and describe artistic strategies that represent the influence of such semantic aspects of the cultural code as the influence of the artistic worldview, the strategies elevation of original interpretation and transformation of the animal style, the influence of the academic background. We define the artistic paradigm of the style as a style-forming factor in contemporary creative industries of artists who emerged from traditional crafts communities. The phenomenon of ethnic artistic tradition has been widely studied in the art history literature (T. M. Stepanskaya, A. V. Edokova, L. I. Nekhlyadovich). We believe, however, that attention should be focused on the content of “cultural code of artistic paradigm”, because ethnic artists consciously transform national artistic images and techniques through integration of their heritage into contemporary artistic language, culture and art background. This is particularly relevant for artists who institutionalize their style into a recognizable contemporary art language strategy. The main research question addressed in this paper is the representation peculiarities of the Namdakov’s artistic strategy semantic forms. He creates innovative ways of shaping, applies illogical, provocative and asymmetrical compositional solutions, creates fresh artistic metaphors, overcomes visual and figurative traditions and transforms ethnic artistic traditions into the leading artistic world-class trends of contemporary art. It has been proved that the animalistic style acquired a new modern dimension with the development of the creative industry in the regions of South-East Asia: the north of modern China and the art workshops of D. Namdakov and Zhigzhit Bayaskhalanov in the Russian Federation. It was the original interpretation of the animalistic style that became a powerful source for the development of traditional folk craft culture and brought the Far East peoples’ modern art to a new level of development, contributed to the evolution of the artist’s creative potential and gave many artists hope for creative expression.